Components of a Research Proposal for the Field of Information and Communication Technology Education - Diyal, Suresh Bahadur; Pandey, Romkant (Innovative Research Journal, 2024)
This article explores the key components of a research proposal, with a specific focus on Information and Communication Technology (ICT) education. It provides a detailed analysis of essential elements such as the background of the study, problem statement, research objectives, research questions, hypothesis, literature review, justification, research methodology, limitations, and definitions of key terms. Using a qualitative research methodology, the study draws on data collected through library research and analyzed through descriptive, analytical, and critical methods. The article emphasizes the importance of a well-structured research proposal as a roadmap for successful research, particularly in the field of ICT education. Aimed at students, educators, researchers, and subject experts. This article serves as a practical guide for constructing effective research proposals, offering valuable insights into the research process and its application in ICT education.